Framework for Dynamic-Stiffness-Based Free Vibration Analysis of Plate-Like Structures - Miroslav Marjanović; Marija Nefovska-Danilović; Emilija Damnjanović (Shock and Vibration)
A framework for free vibration analysis of plate-like structures is presented in the paper. Based on the previously formulated dynamic stiffness elements, FREEVIB object-oriented software in Python environment has been created. Software design and structure as well as a wide range of possible structural problems that could be analyzed using the FREEVIB are presented. Through several illustrative examples including free vibration analysis of stepped, stiffened and folded plate structures, implying isotropic or orthotropic material formulations, the efficiency and accuracy of the FREEVIB is demonstrated. The possibilities of further extensions and improvements of the software are discussed.